My God, why have you abandoned me? Sexual abuse and attitudes towards God among Orthodox Jews - Pirutinsky, Steven (Mental health, religion & culture, 2020)
Childhood sexual abuse (CSA) correlates with disruptions in core beliefs, which within Orthodox Judaism may be linked to God. We hypothesise that CSA may negatively alter attitudes towards God for some, while remaining unchanged or even activating this domain for others. This was tested in a sample of 136 individuals and results indicated that positive explicit beliefs about God differed between those who remained Orthodox and those who disaffiliate regardless of CSA and that negative explicit attitudes differed between those with CSA and those without regardless of religious identity. Participants with CSA who remained Orthodox reported more positive implicit attitudes compared to all other groups, while participants with CSA who disaffiliated reported the least positive attitudes. Divergence between explicit and implicit beliefs suggests that attitudes towards God are multifactorial reflecting both conscious theology and unconscious experiences, and that CSA may have particular influence over these unconscious dimensions.